2016
DOI: 10.1016/j.jpainsymman.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

EffenDys—Fentanyl Buccal Tablet for the Relief of Episodic Breathlessness in Patients With Advanced Cancer: A Multicenter, Open-Label, Randomized, Morphine-Controlled, Crossover, Phase II Trial

Abstract: The description of a faster and greater relief of episodic breathlessness by transmucosal fentanyl versus morphine justifies further evaluation by a full-powered trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 21 publications
0
31
0
3
Order By: Relevance
“…Although only 6 patients were recruited, the investigators reported that FBT had a non-statistically significant trend towards faster onset and greater efficacy for breakthrough dyspnea relief. (21)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although only 6 patients were recruited, the investigators reported that FBT had a non-statistically significant trend towards faster onset and greater efficacy for breakthrough dyspnea relief. (21)…”
Section: Discussionmentioning
confidence: 99%
“…(19, 20) A recent crossover trial of 6 patients reported that FBT had a faster onset of action than oral morphine for episodic dyspnea. (21) A better understanding of FBT's effect on exertional dyspnea may open up novel therapeutic options for this distress symptom. In this pilot placebo-control randomized controlled trial, we estimated the within-arm effects of prophylactic FBT and placebo on the intensity of exercise-induced episodic dyspnea.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary data from a small randomised trial comparing fentanyl buccal tablet with morphine sulfate for treatment of episodic breathlessness suggested that fentanyl had a faster onset and provided greater relief. 71 Several small placebo-controlled trials have examined the use of prophylactic fentanyl given prior to exertion in opioid-tolerant patients with cancer and reported a benefit (discussed below). [72][73][74] Taken together, the available evidence signals that opioids have a positive effect on breathlessness among opioid-tolerant individuals, giving justification for further studies to examine these findings in confirmatory trials and to determine the optimal dose and timing of opioids for breathlessness.…”
Section: Opioidsmentioning
confidence: 99%
“…Breathlessness scores decreased linearly from 10 to 60 min post-treatment completion [ 23 ]. In a randomized cross-over study performed in a real-life clinical setting, focused on exertional EB, the mean times to onset for fentanyl buccal tablet and oral morphine were 12.7 and 23.6 min, respectively [ 24 ]. Considering that about 80% of episodes last ≤10 min, it is likely that the effect is produced by the natural course of EB, with a spontaneous disappearance, particularly when EB is induced by an effort, possibly stopped after EB occurred [ 25 ].…”
Section: Discussionmentioning
confidence: 99%